Preparation of graphene quantum dots as a green photosensitizer and its application in Dye sensitized solar cell / Golnoush Zamiri - Golnoush , Zamiri (2018)
The increasing incidence of global warming provides the impetus for research in alternative green renewable energy sources, such as tidal, geothermal, biomass, wind, and solar energy. Among these options, solar energy is of great interest due to its inherent abundance. Currently, commercially produced solar cells are based on silicon technology, which is very expensive due to the high production costs. An alternative to the conventional Si solar cell is the Dye-Sensitized Solar Cells (DSSCs), which is currently being actively explored. The commonly used dyes for a photosensitizer in DSSCs are ruthenium-based complexes. To improve the performances of DSSCs and to increase their commercial attractiveness, cheap, colorful, stable, and highly efficient ruthenium-free dyes needs to be developed due to ruthenium-based dyes are quite rare. An alternative to dye-type sensitizers are quantum dots (QDs). QDs are interesting due to their intrinsic properties. The band gap varies with size, therefore, absorption and redox properties can be tuned by the synthesis of QDs. Zero-dimensional graphene quantum dots (GQDs) consist of single- or few-layer graphene with a size less than 100nm and stand for a new type of QDs with unique properties combining the graphene nature and size-resulted quantum effects. GQDs possess unique optical and electronic properties, and in particular possess a band-gap less than 2.0 eV because of quantum confinement and edge effects. In this study, we synthesized GQDs from graphene oxide (GO) by using the hydrothermal method. We investigated the performance of DSSCs using different thicknesses of TiO2 and ZnO nanoparticles as photo-anodes and the as-prepared GQD as a green photosensitizer. The I-V test results indicate that the performance of DSSCs is improved by increasing the thickness of the photo-anode and the thickness of 40 μm shows the highest efficiency for both DSSC devices based on TiO2 and ZnO nanoparticles photo-anodes. The DSSCs using TiO2 and ZnO nanoparticles as photo-anodes with thickness of 40 μm show almost same efficiency when we replaced N-719 with GQDs which is confirmed that using GQDs as an alternative to ruthenium based dyes is a new approach for DSSCs.